2003
DOI: 10.1038/sj.bjc.6601276
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of meta-iodobenzylguanidine in neuroendocrine tumours is mediated by vesicular monoamine transporters

Abstract: The radio-iodinated noradrenaline analogue meta-iodobenzylguanidine (MIBG) can be used for scintigraphy and radiation therapy of neuroendocrine (NE). The aim of the present study was to study the importance of vesicular monoamine transporters (VMATs) for the uptake of 123 I-MIBG in NE tumours. In nude mice, bearing the human transplantable midgut carcinoid GOT1, all organs and xenografted tumours accumulated 123 I after i.v. injection of 123 I-MIBG. A high concentration of 123 I was maintained in GOT1 tumours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 14 publications
(14 reference statements)
3
48
0
1
Order By: Relevance
“…We believe that the different capacities in serotonin uptake are due to the different C-terminus of the proteins, which leads to targeting of different cellular compartments. The importance of vesicle proteins in the diagnosis and treatment of neuroendocrine tumors has been discussed, and recently it was demonstrated that VMAT1 is important for the uptake of 123 I-MIGB in tumor cells (Kolby et al 2003, Nilsson et al 2004. This compound has an important role in scintigraphy and radionuclide therapy of neuroendocrine tumors, but whether a relative increase of …”
Section: Kdel (Stornaiuolomentioning
confidence: 99%
“…We believe that the different capacities in serotonin uptake are due to the different C-terminus of the proteins, which leads to targeting of different cellular compartments. The importance of vesicle proteins in the diagnosis and treatment of neuroendocrine tumors has been discussed, and recently it was demonstrated that VMAT1 is important for the uptake of 123 I-MIGB in tumor cells (Kolby et al 2003, Nilsson et al 2004. This compound has an important role in scintigraphy and radionuclide therapy of neuroendocrine tumors, but whether a relative increase of …”
Section: Kdel (Stornaiuolomentioning
confidence: 99%
“…Other strategies in this direction that might be effective include targeting the promoter regions of the norepinephrine transporter gene or increasing the cell-surface expression of the transporter via N-glycosylation regulatory mechanisms [56]. Nevertheless, in addition to the cell membrane norepinephrine transporter, it seems that numbers of neurosecretory granules and the presence of vesicular monoamine transporters (VMATs) are also crucially important for uptake and retention of radiolabeled MIBG [57,58]. Thus, strategies aimed at sensitizing neuroendocrine tumors to drugs targeting the norepinephrine transport and storage system could benefit from approaches that increase expression of all key components of the system.…”
Section: Future Challenges For Effective Treatmentmentioning
confidence: 99%
“…131 I-MIBG is a guanethidine derivative, structurally similar to noradrenaline and thus is accumulated in tissues arising from neural crest cells (Wafelman et al, 1994). 131 I-MIBG is transported by vesicular monoamine proteins and is concentrated in intracellular storage vesicles (Kolby et al, 2003). It is thought that emission of ionising radiation at this site results in tumour decay (Mukherjee et al, 2001;Rose et al, 2003;Pasieka et al, 2004).…”
mentioning
confidence: 99%